Determination of Murabahah Fines at Wates Jaya Phone According to Fatwa DSN MUI No. 17 of 2000 - Cahyaning Puteri, Suci; Asiyah, Binti Nur (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
Wates Jaya Phone is one of the Wates Mulyo BUM Desa business units which is engaged in buying and selling smartphones and other electronic equipment, their buying and selling practices are based on sharia. This financing is murabahah which is used as a principle in buying and selling smartphones that are ordered on a firm basis without a down payment with competitive margins. Unfortunately, even though murabahah installment payments are made very easily, there are still customers who deliberately delay payments and cause significant problems for Wates Jaya Phone. This research aims to analyze the implementation of Murabahah transactions and the determination of Murabahah fines on Wates Jaya cell phones according to the MUI DSN Fatwa Number 17 of 2000. The research method used is descriptive with a qualitative approach using literature studies and case studies on Wates Jaya cellphones. The results of this research show that the murabahah contract carried out on Wates Jaya Phone is carried out with a single contract only (according to Islamic rules and legal rules), in contrast to other sharia institutions mentioned in previous research which camouflage murabahah and wakalah contracts, then determine Murabahah Fines on Wates Jaya Phone is also in accordance with the MUI DSN Fatwa Number 17 of 2000, namely the application of fines following the principle of ta'zir/fines in the form of money amounting to 1.5% of the transaction price plus a margin for each month, outside of transaction financing so that customers are more disciplined, in the future fines.